2022
DOI: 10.1111/puar.13473
|View full text |Cite
|
Sign up to set email alerts
|

Representing Personal and Professional Identities in Policing: Sources of Strength and Conflict

Abstract: Representing diverse identities in government is important for equal employment, symbolic benefits, and opportunities to improve public service outcomes. This article uses qualitative interviews with 32 frontline police officers to examine the ways in which personal and professional identities intersect to promote or impede those benefits. The findings highlight how holding similar sociodemographic identities with the public can be a source of strength as it pertains to promoting shared understanding and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
(71 reference statements)
1
13
0
Order By: Relevance
“…Recently, Pandey, Newcomer, et al (2022) explicitly argue for more race‐aware and gender‐aware scholarship and call for making race and gender central to study of social equity. Their argument for this exhortation is worth repeating (Pandey, Newcomer, et al, 2022, p. 386), “A richer conceptualization of race and gender as social institutions, structures, and processes is essential for a substantive social equity turn in public administration and public policy scholarship.” The recent Public Administration Review Race and Gender symposium has a number of notable contributions that offer a richer perspective on race and/or gender (e.g., Breslin et al, 2022; Headley, 2022; Piatak et al, 2022; Strader & Smith, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pandey, Newcomer, et al (2022) explicitly argue for more race‐aware and gender‐aware scholarship and call for making race and gender central to study of social equity. Their argument for this exhortation is worth repeating (Pandey, Newcomer, et al, 2022, p. 386), “A richer conceptualization of race and gender as social institutions, structures, and processes is essential for a substantive social equity turn in public administration and public policy scholarship.” The recent Public Administration Review Race and Gender symposium has a number of notable contributions that offer a richer perspective on race and/or gender (e.g., Breslin et al, 2022; Headley, 2022; Piatak et al, 2022; Strader & Smith, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Andrea Headley's (2022) research article examines experiences of employees with diverse identities within public organizations, using in‐depth qualitative study of local police officers. She conducted qualitative interviews with 32 frontline police officers to examine the ways in which personal and professional identities intersect to promote or impede benefits of bureaucratic representation.…”
Section: Race and Gender Symposium Contents—research Articles And Vie...mentioning
confidence: 99%
“…Their findings detail Black women's sexual harassment experiences and support their call for addressing sexual harassment in the workplace with an intersectional lens in order to design more inclusive prevention and response policies, and programs. Andrea Headley's (2022) research article examines experiences of employees with diverse identities within public organizations, using in-depth qualitative study of local police officers. She conducted qualitative interviews with 32 frontline police officers to examine the ways in which personal and professional identities intersect to promote or impede benefits of bureaucratic representation.…”
Section: Diversity and Inclusion In Public Organizationsmentioning
confidence: 99%
“…A compelling body of public management research has empirically linked passive to active representation in public organizations, demonstrating that demographic representation makes a clear difference in the enactment of outcomes designed to benefit specific client groups (Capers & Smith, 2021; Headley, 2022; Nicholson‐Crotty et al, 2011; Wilkins & Kaiser, 2006). Some research, for example, has demonstrated that when organizational structures permit higher levels of administrative discretion to those directly carrying out the work of the agency, policy outcomes favoring minority interests are more likely to result (Meier & Bohte, 2001; Sowa & Selden, 2003).…”
Section: Theoretical Insights From Social Equity Representation and P...mentioning
confidence: 99%